Desigualdad y desarrollo en América Latina: 1960-2010. Argentina-Chile-Colombia-Perú - Noejovich Chernoff, Héctor Omar (2012)
This paper aims to set a comparative point of view for the development process within four countries. In this case development is understood in a wide sense far from a merely growth and per capita income